Induced photoemission from driven nonadiabatic dynamics in an avoided crossing system - Arasaki, Yasuki; Scheit, Simona (The journal of chemical physics, 2014)
When vibrational dynamics on an ionic state (large dipole moment) is coupled to that on a neutral state (small dipole moment) such as at an avoided crossing in the alkali halide system, the population transfer between the states cause oscillation of the molecular dipole, leading to dipole emission. Such dynamics may be driven by an external field. We study how the coupled wavepacket dynamics is affected by the parameters (intensity, frequency) of the driving field with the aim of making use of the photoemission as an alternative detection scheme of femtosecond and subfemtosecond vibrational and electronic dynamics or as a characteristic optical source.